Contribution to the histopathology of the liver in pellagra - Díaz Encinas, Jorge (1948)
This work aims to study pellagra prevalent disease in our country, which has a direct causal relationship with deficiency factors, having the possibility that they may be increased because of increasing economic order of our time. Moreover, the existence of numerous clinical conditions indefinitely but grouped under the general heading of "Avitaminosis" physiognomy, lead me to verify a brief review of the disease only from the angle of the liver histopathology.